Shocks as causes of turnover: What they are and how organizations can manage them - Holtom, Brooks C.; Mitchell, Terence R.; Lee, Thomas W.; Inderrieden, Edward J. (Human Resource Management, 2005)
Voluntary employee turnover is expensive. Companies that successfully retain the best and brightest employees save money and protect their intellectual capital. Traditional approaches to understanding turnover place accumulated job dissatisfaction as the primary antecedent to voluntary turnover. However, we show that precipitating events, or shocks, more often are the immediate cause of turnover. Using data from more than 1,200 “leavers,” we describe the nature, content, and role of shocks in turnover decisions. We then provide strategies to help organizations manage shocks, and thereby control turnover. © 2005 Wiley Periodicals, Inc.